A caged tris(2-pyridylmethyl)amine ligand equipped with a Ctriazole–H hydrogen bonding cavity. Issue 28 (20th May 2022) - Qiu, Gege; Diao, Donglin; Chaussy, Leo; Michaud-Chevallier, Sabine; Simaan, A. Jalila; Nava, Paola; Martinez, Alexandre; Colomban, Cédric
Abstract : The first TPA ligand equipped with a well-defined triazole-based hydrogen bonding cavity, inspired from the functionalized cavities of enzymes, was prepared. Abstract : A capped bioinspired ligand built from a tris(2-pyridyl-methyl)amine (TPA) unit and surmounted by a triazole-based intramolecular H-bonding secondary sphere was prepared. The resulting cage provides a well-defined cavity combining the hydrophobic nature with H-bonding properties. Its coordinating properties were explored using Zn(ii ) and Cu(ii ) metal ions.